Endocannabinoid gene × gene interaction association to alcohol use disorder in two adolescent cohorts - Elkrief, Laurent; Spinney, Sean; Vosberg, Daniel E.; Banaschewski, Tobias; Bokde, Arun L. W.; Quinlan, Erin Burke; Desrivières, Sylvane; Flor, Herta; Garavan, Hugh; Gowland, Penny; Heinz, Andreas; Brühl, Rüdiger; et al. (Frontiers in psychiatry, 2021)
Genetic markers of endocannabinoid system have been linked to a variety of addiction-related behaviours that extend beyond cannabis use. In the current study we investigate the relationship between eCB genetic markers and AUDs in European adolescents (14-18 years old), followed in the IMAGEN study (n=2051) and explore replication in a cohort of North American adolescents from Canadian Saguenay Youth Study (SYS) (n=772). Case-Control status is represented by a score of more than 7 on the Alcohol Use Disorder Identification Test (AUDIT). First a set-based test method was used to examine if a relationship between the eCB system and AUDIT case/control status exists, at the gene level. Using only SNPs that are both independent and significantly associated to case-control status, we perform Fisher’s exact test to determine SNP level odds ratios in relation to case-control status and then perform logistic regressions as post-hoc analysis, while considering various covariates. Generalized multifactor dimensionality reduction (GMDR) was used to analyze the most robust SNP x SNP interaction of the 5 eCB genes with positive AUDIT screen. While no gene-sets were significantly associated to AUDIT scores after correction for multiple tests, in the case/control analysis, 7 SNPs were significantly associated with AUDIT scores of > 7 (p<0.05; OR<1). Two SNPs remain significant after correction by false discovery rate (FDR); rs9343525 in CNR1 (pcorrected=0.04273, OR=0.729) and rs507961 in MGLL (pcorrected=0.04273, OR=0.784). Logistic regression showed that both rs9353525 (CNR1) and rs507961 (MGLL) remained significantly associated with positive AUDIT screens (p<0.01; OR<1), after correction for multiple covariables and interaction of covariable x SNP. This result was not replicated in the SYS cohort. The GMDR model revealed a significant three-SNP interaction (p= 0.006) involving rs484061 (MGLL), rs4963307 (DAGLA) and rs7766029 (CNR1) predicted case-control status, after correcting for multiple covariables in the IMAGEN sample. A binomial logistic regression of the combination of these three SNPs by phenotype in the SYS cohort showed a result in the same direction as seen in the IMAGEN cohort (BETA=0.501, p=0.06). While preliminary, the present study suggests that the eCB system may play a role in the development of AUD in adolescents.
Gesehen am 14.07.2021